The inclusive approach to talent identification and development for Japanese Paralympic athletes - Kinugasa, T.; Kojima, Y. (Journal of High Performance Sport, 2020)
The uniqueness of Paralympic sport or para-sport is evident in the practical tasks necessary for athletes with physical disabilities to participate in para-sport and to continue to being involved. Classification is also an unique system to promote para-sport participation by minimizing the impact of impairment on the outcome of competition. Thus, the inclusive and quality participation framework is needed, and the classification system is the integral part of the process of athlete development in para-sport. The aim of the study was to conduct an environmental scan in para-sport and discuss talent identification and development for Japanese Paralympic athletes. The National Talent Identification and Development (NTID) program in Olympic sport was strategically implemented by Japan Sport Council (JSC) in 2012 as a new national project to identify, confirm, and develop pathways of medal potential athletes. Before implementing the NTID program in para-sport, the 3C`s (Customer, Company, and Competitor) model was used as a marketing tool to analyze the current sporting environment in para-sport. Based on the current analysis, a biological and inclusive approach was taken in NTID by considering sports science testing and classification for para sports etc. Ten athletes were identified by National Federations from 56 participants over 2 years from 2017 to 2018, and they are currently aiming to become future medalists. Ultimately, NTID is an entry point to high performance sport and is a part of whole of the athlete development pathway for Japanese Paralympic athletes. In future, JSC will continue to work on talent identification and development programs with key stakeholders by integrating Olympic sport and para-sport to promote participation and increase the talent pool in para-sport.